-3k+5(6-k)=4(1-2k)+6

Simple and best practice solution for -3k+5(6-k)=4(1-2k)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3k+5(6-k)=4(1-2k)+6 equation:


Simplifying
-3k + 5(6 + -1k) = 4(1 + -2k) + 6
-3k + (6 * 5 + -1k * 5) = 4(1 + -2k) + 6
-3k + (30 + -5k) = 4(1 + -2k) + 6

Reorder the terms:
30 + -3k + -5k = 4(1 + -2k) + 6

Combine like terms: -3k + -5k = -8k
30 + -8k = 4(1 + -2k) + 6
30 + -8k = (1 * 4 + -2k * 4) + 6
30 + -8k = (4 + -8k) + 6

Reorder the terms:
30 + -8k = 4 + 6 + -8k

Combine like terms: 4 + 6 = 10
30 + -8k = 10 + -8k

Add '8k' to each side of the equation.
30 + -8k + 8k = 10 + -8k + 8k

Combine like terms: -8k + 8k = 0
30 + 0 = 10 + -8k + 8k
30 = 10 + -8k + 8k

Combine like terms: -8k + 8k = 0
30 = 10 + 0
30 = 10

Solving
30 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -10+2x=5x-31 | | 4x^3+3x^2=4X+3 | | 6+6q=11+5q | | 5(22+-2y)-2y=-10 | | -1(-4)= | | 2y-6x=5 | | 6x^2+30=0 | | 10a-15b= | | 0=-2x+4x+4 | | 152=x+x+2(2x-16) | | x*x+7x=7 | | -0.01*x+60=0 | | 3x+-y=-1 | | -3x+3=6-4x | | V+lwh= | | -0.01*x+60=25 | | x/x+7x=7 | | -3c+11A-5a-11c+9c= | | (XxX)+7x=7 | | 1+6x=4x-11 | | x+7x=7 | | fx=x^2+3 | | -0.1*x+60=25 | | 1-2x(5+x)=7 | | (x+4)(x-2)=112 | | 3u^2-75=0 | | Y^2-2y-13=0 | | 2a-5(a+1)=0 | | 3a+2a-a=24 | | x(x+5)-10=x^2-2x+4 | | 2b-7=21 | | h+5h-3-6h=0 |

Equations solver categories